2004
DOI: 10.1387/ijdb.031748js
|View full text |Cite
|
Sign up to set email alerts
|

Developing chick embryos express a protein which shares homology with the nuclear pore complex protein Nup88 present in human tumors

Abstract: Nup88 is a nuclear pore complex protein which is overexpressed in a variety of human tumors of the stomach, colon, liver, pancreas, breast, lung, ovary, uterus, prostate and kidney. A monoclonal antibody crossreacting with the yeast Candida albicans and Nup88 was used to investigate the expression of cross-reactive antigens in chick embryos, in an attempt to identify an experimental model for studying the role played by Nup88 during cell development and differentiation. All cells in the trilaminar embryo were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The similarities shown by Mabs C7 and C6 suggested that Mab C7 might also react with Nup88. This possibility has been recently confirmed using a 27 kDa recombinant fragment from Nup88 obtained in Escherichia coli [58].…”
Section: Antitumor Activity Of Mab C7mentioning
confidence: 83%
See 1 more Smart Citation
“…The similarities shown by Mabs C7 and C6 suggested that Mab C7 might also react with Nup88. This possibility has been recently confirmed using a 27 kDa recombinant fragment from Nup88 obtained in Escherichia coli [58].…”
Section: Antitumor Activity Of Mab C7mentioning
confidence: 83%
“…The diagnostic usefulness of Mab C7 was studied by means of immunohistochemistry in a series of ovarian cancers, showing a granular staining with marked perinuclear accumulation (Figure 11). However, Mab C7 showed a more diffuse cytoplasmic pattern in oral squamous cell carcinomas [58].…”
Section: Biological Activities Of Mab C7mentioning
confidence: 89%
“…The polyclonal rabbit antiserum against Nup88 was the same employed in previous studies by our group [5][6][7][8][10][11][12] . The preparation, specificity and reliability of the rabbit polyclonal Nup88 antibody used in this study were as described previously [5][6][7][8][10][11][12] .…”
Section: Immunohistological Staining and Evaluationmentioning
confidence: 99%
“…The preparation, specificity and reliability of the rabbit polyclonal Nup88 antibody used in this study were as described previously [5][6][7][8][10][11][12] .…”
Section: Immunohistological Staining and Evaluationmentioning
confidence: 99%
“…8 Subsequently, we studied Nup88-mRNA expression in breast cancer and showed it to be associated with all clinical and biological features defining a significantly more aggressive tumor phenotype. 9 From these results, we concluded that Nup88 could serve as a new biological marker of aggressiveness in breast cancer.…”
mentioning
confidence: 99%